Here is the Place to Begin Your Explorations: An Autoethnographical Examination into Student Teaching Abroad - Amanda D. Lickteig; Josie Rozell; Ashley Peterson (Educational Considerations, 2019)
Participation in study abroad programs has increased steadily since the late 1980s and has tripled in the past two decades. Benefits of these experiences include positive academic performance, improved mental health, and better professional development—but for pre-service teachers who study abroad, these positive benefits can also transfer into culturally relevant pedagogy. As the need for teacher preparation programs to equip their students with global competence grows, cultivating undergraduates’ abilities to appreciate diverse perspectives not only empowers them to thrive in an interconnected world but also enables them to meet the academic and social needs of their culturally diverse students. In this paper, the authors use an assortment of methods (such as classroom observations, research journals, artifacts, and freewriting) to document and reflect on their international student teaching practicums. Autoethnography serves as a methodological vehicle to promote reflection on personal experiences embedded within larger cultural contexts. These narratives are then filtered through the theoretical framework of transformative learning theory to produce reflective analyses of our habits of mind and cultivate autonomous thinking.
Keywords: study abroad; student teaching; autoethnography; transformative learning theory